Human Resources Competency In Improving Employee Performance - Yolanda, Riska Dwi; Hidayat, Syamsul; Hamidah, Hamidah (Bina Bangsa International Journal of Business and Management, 2021)
Each company is formed to achieve a specific goal and it is said to be successful when it has been achieved is necessary to achieve success incompetent human resources. There are competence becomes very useful to help organizations to improve their performance. This research aims to specify the influence of knowledge competence, skills, and attitudes on employee performance at PT. Nikomas Gemilang. The Data were collected using the method of survey, interviews, a questionnaire with 100 respondents. The data were analyzed using quantitative descriptive analysis and Partial least square structural equation modeling (PLS-SEM). The analyzed model of the equation is the outer model, the inner model, and the hypothesis testing. Based on the results of the calculations using software SmartPLS version 3.3.2 for Windows has a significant influence on the employee's performance with the value of 2.545 significance of 0.011, the value of significance is less than 0.05. Knowledge has no significant effect on the employee's performance with a value of 1.705 in its significance of 0.089 more than 0.05. Attitudes have a significant influence on the performance of employees with the statistical value of 3.313 significance value 0.001, a significant value is less than 0.05. Conclusion Skills and attitudes have a positive influence on employee performance and knowledge does not influence employee performance